ANALISIS KUAT TEKAN BETON DENGAN AGREGAT PASIR DARI BOYOLALI MENGGUNAKAN BAHAN TAMBAH ABU SEKAM PEMBAKARAN KAYU DAN SERBUK HALUS ARANG BRIKET - Timbul Catur Suwiyono; Purwanto Purwanto; Anik Kustirini (Universitas Semarang, 2018)
Concrete research has been carried out, this study utilizes wood burning husk ash and fine powder of briquette charcoal as an added material from the weight of cement and sand used from Boyolali. This study aims to determine the compressive strength of concrete with materials added to wood burning husk ash and fine powder of briquette charcoal. Material variations added wood burning husk ash and briquette charcoal fine powder by 0%, 10%, 20% by weight of cement. This study used 0.5 fas and concrete testing at the age of 7 days, 14 days and 28 days. From the test results the average compressive strength of concrete at the age of 7 days with a material variation of 10% added was 15.05 MPA, and a material variation of 20% added was 13.47 MPA. Concrete at the age of 14 days with a material variation of 10% added is 15.76 MPA, and a material variation of 20% is 13.18 MPA. concrete at 28 days with a material variation of 10% added is 14.32 MPA, and a 20% added material variation is 14.32 MPA. Keywords; wood burning husk ash, compressive strength, fine briquette charcoal powder AbstrakPenelitian beton telah banyak dilakukan, penelitian ini memanfaatkan abu sekam pembakaran kayu dan serbuk halus arang briket sebagai bahan tambah dari berat semen dan pasir yang digunakan dari boyolali. Penelitian ini bertujuan untuk mengetahui kuat tekan beton dengan bahan tambah abu sekam pembakaran kayu dan serbuk halus arang briket. Variasi bahan tambah abu sekam pembakaran kayu dan serbuk halus arang briket sebesar 0%, 10%, 20% dari berat semen. Penelitian ini menggunakan fas 0,5 dan pengujian beton pada umur 7 hari, 14 hari dan 28 hari. Dari hasil pengujian kuat tekan rata-rata beton pada umur 7 hari dengan variasi bahan tambah 10% adalah 15,05 MPA, dan vari asi bahan tambah 20% adalah 13,47 MPA. Beton pada umur 14 hari dengan variasi bahan tambah 10% adalah 15,76 MPA, dan variasi bahan tambah 20% adalah 13,18 MPA. beton pada umur 28 hari dengan variasi bahan tambah 10% adalah 14,32 MPA, dan vari asi bahan tambah 20% adalah 14,32 MPA. Kata kunci : abu sekam pembakaran kayu, kuat tekan, serbuk halus arang briket